EXAMINING ENGLISH LANGUAGE LEARNING CHALLENGES IN SULAYMANIYAH PRIMARY SCHOOLS: A COMPARATIVE CASE STUDY - Muhammed, Areen Ahmed (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This research investigates the challenges faced by primary school students in Sulaymaniyah City/Kurdistan Region/Iraq in learning English, focusing on both public and private schools. The main objective of the research is to discover the contradictory approaches to English language learning among primary school students, particularly concerning the influence of teachers and the surrounding educational environment in public and private primary schools in Kurdistani Iraq. By analyzing data collected through questionnaires (n=100) which were 15 statements to be answered and interviews (n=4) with students and teachers which were 3 questions to be asked, the research highlights significant differences in the English language learning experiences between public and private schools. The key findings of this research reveal that students’ proficiency in English is influenced by various factors, including their motivation, family background, and school environment. Moreover, teachers’ instructional methods play a crucial role, as students benefit from engaging and diverse teaching strategies. Furthermore, the research underscores that a supportive and well-resourced learning environment—characterized by adequate classroom facilities, minimal noise, and effective teaching materials—significantly impacts students’ ability to learn English. The research suggests that enhancing teacher training, updating classroom resources, and fostering supportive home environments could improve English language learning outcomes for students across both types of schools. Overall, this comparative case study provides valuable insights into how different educational contexts influence English language acquisition. The research offers recommendations for improving educational practices in primary schools generally and public schools, specifically in the Kurdistan Region of Iraq.